Secondary Intra-Abdominal Pregnancy: A Case Report - Shanbhag, A; Singh, A (Nepal Journal of Obstetrics and Gynaecology, 2012)
Abdominal pregnancy is extremely rare, and has been historically defined as an implantation in the peritoneal cavity exclusive of tubal, ovarian and intraligamentary pregnancy. Abdominal pregnancy can be primary or secondary. The presence of abdominal pregnancy is associated with increased maternal and perinatal morbidity and mortality. The reported incidence of abdominal pregnancy ranges from 1 per 2200 to 1 per 10,200 pregnancies1. The early recognition and management of the same is necessary to prevent untoward complications. This case report describes an interesting case of a 16 year primigravida with a live secondary abdominal pregnancy. NJOG 2011 Nov-Dec; 6 (2): 44-46 DOI: http://dx.doi.org/10.3126/njog.v6i2.6756